2013
DOI: 10.1007/s13384-013-0105-0
|View full text |Cite
|
Sign up to set email alerts
|

Education research in Australia: where is it conducted?

Abstract: Research assessment exercises aim to identify research quantity and quality and provide insights into research capacity building strategies for the future. Yet with limited knowledge of the ecology of Australian educational research, there is little chance of understanding what research audits might contribute towards a capacity building agenda for such a complex field. This paper draws on secondary data analysis of research outputs submitted by 13 Australian higher education institutions to the Excellence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…In nations like Australia and the UK, funding for institutions is based on academic research output -which includes winning competitive funding and publishing research findings (see discussions of the RAE exercise in the UK by Prowle 2013 and the ERA exercise in Australia by Bobis et al 2013). For many academic staff working in universities around the world, being an "author" of textual products is a critical part of their job descriptions, their institutional roles, not to mention their own sense of academic identity (MacSherry 2000;Galloway and Jones 2012;Taylor 2001).…”
Section: Authorship and Plagiarism Policiesmentioning
confidence: 99%
“…In nations like Australia and the UK, funding for institutions is based on academic research output -which includes winning competitive funding and publishing research findings (see discussions of the RAE exercise in the UK by Prowle 2013 and the ERA exercise in Australia by Bobis et al 2013). For many academic staff working in universities around the world, being an "author" of textual products is a critical part of their job descriptions, their institutional roles, not to mention their own sense of academic identity (MacSherry 2000;Galloway and Jones 2012;Taylor 2001).…”
Section: Authorship and Plagiarism Policiesmentioning
confidence: 99%
“…The AARE/ACDE project revealed that the educational research community in Australia was spread among researchers in Education ‘academic organisational units’ (AOUs) classifying their research outputs as belonging to the Education ‘field of research’ (FoR), researchers in education AOUs perceiving their research as belonging to other FoRs, and researchers in other AOUs perceiving their research as belonging to the education FoR. Bobis et al (2013) reported that the proportion of education FoR submissions to ERA 2010 for education AOUs was 54.6% and in ERA 2012 this increased to 59.3%. ERA 2010 covered 20% of research published between 2003 and 2008, and ERA 2012 covered 30% of research published between 2005 and 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Educational research for ERA was coded into four categories: Education Systems; Curriculum and Pedagogy; Specialist Studies in Education; and Other Education. The group of leading Australian research-intensive universities, the so-called Group of Eight produced 54% of the education FoR submissions in ERA 2010 and 60% in ERA 2012 (Bobis et al, 2013). Bobis et al (2013) pointed out that the Education FoR should not be considered as synonymous with educational research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations